The transcriptional regulator CtrA controls gene expression in Alphaproteobacteria phages: Evidence for a lytic deferment pathway - Mascolo, Elia; Adhikari, Satish; Caruso, Steven M.; deCarvalho, Tagide; Folch Salvador, Anna; Serra-Sagristà, Joan; Young, Ry; Erill, Ivan; Curtis, Patrick D. (Frontiers in Microbiology, 2022)
Pilitropic and flagellotropic phages adsorb to bacterial pili and flagella. These phages have long been used to investigate multiple aspects of bacterial physiology, such as the cell-cycle control in the Caulobacterales. Targeting cellular appendages for adsorption effectively constrains the population of infectable hosts, suggesting that phages may have developed strategies to maximize their infective yield. Brevundimonas phage vB_BsubS-Delta is a recently characterized pilitropic phage infecting the Alphaproteobacterium Brevundimonas subvibrioides. Like other Caulobacterales, B. subvibrioides divides asymmetrically and its cell cycle is governed by multiple transcriptional regulators, including the master regulator CtrA. Genomic characterization of phage vB_BsubS-Delta identified the presence of a large intergenic region with an unusually high density of putative CtrA-binding sites. A systematic analysis of the positional distribution of predicted CtrA-binding sites in complete phage genomes reveals that the highly skewed distribution of CtrA-binding sites observed in vB_BsubS-Delta is an unequivocal genomic signature that extends to other pili- and flagellotropic phages infecting the Alphaproteobacteria. Moreover, putative CtrA-binding sites in these phage genomes localize preferentially to promoter regions and have higher scores than those detected in other phage genomes. Phylogenetic and comparative genomics analyses show that this genomic signature has evolved independently in several phage lineages, suggesting that it provides an adaptive advantage to pili/flagellotropic phages infecting the Alphaproteobacteria. Experimental results demonstrate that CtrA binds to predicted CtrA-binding sites in promoter regions and that it regulates transcription of phage genes in unrelated Alphaproteobacteria-infecting phages. We propose that this focused distribution of CtrA-binding sites reflects a fundamental new aspect of phage infection, which we term lytic deferment. Under this novel paradigm, pili- and flagellotropic phages exploit the CtrA transduction pathway to monitor the host cell cycle state and synchronize lysis with the presence of infectable cells.